Butterfiles - Neville, Alexandra (Revista Espaço Acadêmico, 2021)
Some sunny day awhile ago while driving, a butterfly hit the windshield of my car and from its wings left behind a feathery mark of powdered pigment. Someone once told me that if a butterfly’s coloring were rubbed off, it would die. I thought about this as I studied the orange and brown pattern on the glass.